EKSTRAKSI SILIKON DIOKSIDA DARI SEKAM PADI DENGAN METODE PIROLISIS - Prima, Hoddi; Hidayat, Taufik; Mulyadi, Mulyadi (Jurusan Teknik Mesin, Fakultas Teknologi Industri, Institut Teknologi Medan (ITM), 2018)
The aim of this study is to extract silicon dioxide (SiO2) from rice huskby using a self-made pyrolysis furnace. Silicon oxide can be further processed with higher temperature to form silicon carbide (SiC). Either, SiO2and SiC are very useful filler in composite materials. Pyrolysis furnace has a burning chamber made of steel with 60 cm in length and 30 cm in diameter. The thickness of the chamber is 5 mm. Liquefied petroleum gas (LPG) was utilized to heat the chamber from the outside. Rice husk was place inside the chamber and it is compulsory to burn rice husk in the chamber without the presence of oxygen. Chamber vacuuming could be achieved by flowingnitrogen gas into chamber. Chamber pressure was maintained in 3 bar and output valve was opened slowly to get rid of oxygen from chamber while nitrogen flowrate was maintained in 2 liter per minute. Maximum temperature could reach by the furnace was 622 degree Celsius and burning time was set up for two until three hours. It was 200 gram of rice husk can be processed at a time. Further processed was needed on the burnt rice husk by grinding it using ball mill and screening to separate SiO2 and impurities. Chloride acid was used to clean SiO2 and rinsed it with distillation water. SiO2 was dried in room temperature. Thermogravimetric analysis indicated that 64.5 % of SiO2 could be extracted from rice husk.